2016
DOI: 10.1111/radm.12182
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge transfer in university quadruple helix ecosystems: an absorptive capacity perspective

Abstract: Increased understanding of knowledge transfer (KT) from universities to the wider regional knowledge ecosystem offers opportunities for increased regional innovation and commercialisation. The aim of this article is to improve the understanding of the KT phenomena in an open innovation context where multiple diverse quadruple helix stakeholders are interacting. An absorptive capacity-based conceptual framework is proposed, using a priori constructs which portrays the multidimensional process of KT between univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(160 citation statements)
references
References 69 publications
4
131
0
4
Order By: Relevance
“…First it contributes to the growing debate on the strategic challenges of managing knowledge transfer activities (Perkmann et al 2013;Witty 2013;Dowling 2015;Miller et al 2016) and offers practical solutions through meta-rules could facilitate intra-institutional strategic alignment at the corporate, departmental and project level and resolve internal and external stakeholder tensions (Schultz and Hatch 2005;Carter et al 2008). 'Meta-rules' will be of use to KTO managers to overcome challenges evident within each structural level of abstraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First it contributes to the growing debate on the strategic challenges of managing knowledge transfer activities (Perkmann et al 2013;Witty 2013;Dowling 2015;Miller et al 2016) and offers practical solutions through meta-rules could facilitate intra-institutional strategic alignment at the corporate, departmental and project level and resolve internal and external stakeholder tensions (Schultz and Hatch 2005;Carter et al 2008). 'Meta-rules' will be of use to KTO managers to overcome challenges evident within each structural level of abstraction.…”
Section: Discussionmentioning
confidence: 99%
“…Organisational factors have also been found to affect the motivation and willingness of academics to engage in knowledge transfer (Siegel et al 2003;Perkmann et al 2013;Miller et al 2016). Knowledge transfer activities do not always fit within the norms of traditional universities where reward and promotional mechanisms are often focused on publications, funding, teaching and technology commercialisation activities (Miller et al 2014).…”
Section: Organizational Factors Affecting Knowledge Transfermentioning
confidence: 99%
“…From the above paragraph, empirical evidence clearly shown that social innovation as a new innovation outcome strategy are linked positively with knowledge resource in producing highly innovative products, processes and services that in turn provide a significant benefits on social, economic and commercial aspects to the wider society, private and also for the government in particular [38]. Contrary to technological innovation which is said to have limited offers towards merely fulfilling private needs.…”
Section: Social Innovation and Knowledge Resourcementioning
confidence: 99%
“…Hence, a better understanding on social innovation as a new innovation outcome strategy must be internalized by all actors involved in the Malaysian KTP projects. It is evidence that, various actors within the Malaysian KTP projects have diverse objectives, interest and priorities towards their involvement in the Malaysian (RMK-11;2016-2020 with the theme "anchoring growth on people" in lights of fulfilling Malaysia to achieve a high income country status …”
mentioning
confidence: 99%
“…Some empirical studies (Walter et al, 2006;Miller et al, 2016) show that the ability of researchers to establish strategical relations with industry and end-users increases the chances of successful implementation of the innovative project. The dense network of contacts allows easier estimating of the market potential, developing a strategy for the protection of intellectual property rights, prototyping.…”
Section: Entrepreneurial Experience and Its Role In Spin-off Developmentmentioning
confidence: 99%